Child abuse and academic performance of adolescents in Lesotho - a qualitative study - Monyane, 'Makhojane (University of the Free State, 1999)
English: Child abuse refers to the intentional use of force aimed at injuring or damaging the child. Abused children are in most cases characterised by a low self concept misbehaviour such as delinquency and truancy, inadequate language development, depression, negativism and abused children appear to be anti-social. The statement of the problem for this study is whether a relationship exists between child abuse and academic performance. The study focuses on a group of adolescents at SOS school and Hleoheng primary school in Lesotho. The objectives of this investigation are to show how child abuse can affect the academic performance of a child and to identify subsequent behavioural changes of abused children. The family and the school as the child's educational environments, are further investigated and ways in which these institutions can be the major sources of child abuse are studied. The causes and types of child abuse are also investigated. In this study related local and international literature on child abuse and academic performance were reviewed. A group of abused adolescents from SOS school and Hleoheng primary in Lesotho were used as the target group for the purpose of this study. Structured interviews were used to collect data on the family background of abused children, the type of abuse they experienced, their emotions, how they relate with other people, their concentration potential, and specific characteristics that can be attributed to poor academic performance. The first part of the study defines the concept of child abuse. The general causes and types of child abuse are examined. Numerous factors influence parents or anybody in loco parentis to abuse children. In the same way, it has also been discovered that children can also be perpetrators of child abuse. Parents, however, abuse children differently, resulting in various forms of abuse namely physical, sexual, emotional and economic abuse as well as neglect. Ideally, it is expected that a child's home is the best place of the upbringing of a child. Therefore, it follows that the family of a child is charged with the responsibility of nurturing a developing child. The school on the other hand should supplement the child's family to help the child realise his or her abilities. The family and the school are regarded as the major educational environments of a child. The lack of responsible adult intervention and guidance based on the principles of love, warmth and security in the life of a child results in many families and schools being the institutions of abuse of children. Hence, the ideal functions of both the family and the school are changed. The children thus find themselves being abused in the privacy of their own homes and in the school environment. The abused children consequently fail to perform well academically due to these complications in their upbringing. At present, only SOS school in Lesotho reach out to these children in an endeavour to educate them despite their early life experiences. However, due to the rapid increase in the number of abused children in Lesotho, SOS school is not in a position to cater for all these children. This research confirms the relationship between child abuse and academic performance.

Afrikaans: Kindermishandeling is die doelbewuste gebruik van geweld met die oog op die besering of benadeling van die kind. Mishandelde kinders word in die meeste gevalle gekarakteriseer deur In lae selfbeeld, wangedrag soos jeugmisdaad en stokkiesdraai, ongenoegsame taalontwikkeling, depressie, negativisme en In neiging om anti-sosiaal te wees. Die probleemstelling van die studie is om vas te stelof daar 'n verband is tussen kindermishandeling en akademiese prestasie. Die studie fokus op In groep adolessente van SOS-skool en Hleoheng primêre skool in Lesotho. Die doel van die ondersoek is om aan te toon hoe kindermishandeling die akademiese prestasie van In kind kan beïnvloed sowel as die gevolglike gedragsverandering van die mishandelde kind. Die gesin en die skool as die opvoedkundige ongewing van die kind word verder bestudeer asook maniere waarop hierdie instellings bronne kan wees van kindermishandeling. Die oorsake van en tipes kindermishandeling word ook ondersoek. In hierdie studie word relevante plaaslike en internasionale literatuur bestudeer. 'n Groep mishandelde adolessente van SOS-skool en Hleoheng primêre skool in Lesotho is gebruik as respondente. Gestruktureerde onderhoude is gebruik om data te versamel vir die doel van die studie. Familie-agtergrond, die tipe mishandeling, emosies, sosiale verhoudings, konsentrasie-vermoëns, potensiaal en spesifieke karaktertrekke is verder bestudeer as moontlike invloede op akademiese prestasie. Die eerste deel van die studie definieer die konsep kindermishandeling. Die algemene oorsake en tipes kindermishandeling word bestudeer. Verskeie faktore beïnvloed ouers, of enige een wat in loco parentis optree om kinders te mishandel. Soortgelyk kan aangetoon word dat kinders self ook skuldig kan wees aan kindermishandeling. Ouers mishandel kinders egter op In verskeidenheid van maniere soos, onder andere, fisiese, seksuele, emosionele en ekonomiese mishandeling, sowel as verwaarlosing. Die ideaal is dat die kind se huis die beste plek is vir sy opvoeding. Dit volg dus dat die gesin verantwoordelikheid moet dra vir die beswil van die ontwikkelende kind. Die skool, aan die ander kant, moet die kind tot hulp wees om sy of haar vermoëns te realiseer. Die gesin en die skool word beskou as die belangrikste opvoedkundige omgewings van die kind. Die gebrek aan verantwoordelike volwasse intreding en leiding gebaseer op beginsels van liefde, warmte en sekuriteit in die kind se lewe kan lei tot die funksionering van die gesin en die skool as instellings van mishandeling. Op so In wyse word die funksies van die gesin en die skool verander. Kinders word dus mishandel binne die struktuur van die gesin en die omgewing van die skool. Die mishandelde kinders presteer gevolglik swak akademies. Huidiglik reik SOS-skool in Lesotho uit na hierdie kinders in In poging om hulle op te voed ten spyte van vroeë lewensondervindings. Ongelukkig kan SOS-skool nie voorsien in die behoefte van hierdie vinnig-groeiende getal mishandelde kinders. Hierdie navorsing bevestig die verband tussen kindermishandeling en akademiese prestasie.
Keywords: Child abuse -- Lesotho; Academic achievement -- Lesotho; Child abuse; Dissertation (M.Ed. (Psychology of Education))--University of the Free State, 1999